INDUCTION OF GASTRIC MUCUS BY DRAGON’S BLOOD (Croton palanostigma) - SANDOVAL, MIGUEL (2002)
OBJECTIVE: To determine if dragon’s blood Croton palanostigma induces gastric mucus secretion as a protective effect. MATERIAL AND METHODS: Adult male albine 200 to 250 g rats were distributed in 4 groups: (I) control with saline solution; (II) gastric croton 0,8 mL/ kg; (III) duodenal croton 0,8 mL/kg; (IV) ranitidine 50 mg/kg; 10 animals in each group. One hour later, pyloric ligation by abdominal laparatomy was performed under ethil ether anestesia and a histamine discharge was done to stimulate secretion. Stomachs were removed and at the glandular portion mucus secretion was measured by modified Corne method expressed as µg of alcian blue/mL/g of tissue. RESULTS: Mucus production by groups was: control 34,5±5,5; gastric croton 45,8±12,2; duodenal croton 50,6±13,9; ranitidine 39,0±7,1. There was significative more mucus production in the gastric and duodenal croton groups than in the control group p<0,01; there was no difference between ranitidine and control groups. Best croton induction was via duodenum, indicating that mechanism is not solely topical, to be confirmed in future studies. CONCLUSIONS: We found induction of gastric mucus production following application of dragon’s blood croton palanostigma via stomach and duodenun and this could be part of the croton’s protection mechanism.